Governmental Policies in Managing COVID-19 Pandemic: Comparative Study Between Indonesia and Vietnam, Period of January – March 2020 (Jurnal Ilmu Kesehatan Masyarakat, 2021)
Since WHO declared COVID-19 as a global pandemic, COVID-19 management has become a problem for countries with limited resources and weak health systems. The purpose of this article is to describe the implementation of policies in Indonesia and Vietnam, in which both countries have limited resources in facing the COVID-19 pandemic. The present study is a narrative review which compares he COVID-19 policies in two countries. The study is conducted by searching relevant literature on Google Scholar with the keywords "Penerapan Kebijakan COVID-19 di Indonesia", "COVID-19 policy responses in Vietnam", "lesson from limited resource country to control COVID-19", and also scrutinizing the official website managed by the Indonesian Ministry of Health and the Vietnam Ministry of Health. The inclusion criteria are open access papers published between December 2019 and March 2020 in the form of original articles and review articles. This study found the differences in policy implementation between Indonesia and Vietnam in terms of the number of policies, implementation time, scope, and the basis for making policy decisions. Unlike Indonesia, the implementation of policies carried out in Vietnam is more anticipatory, based on previous experience in dealing with the SARS epidemic in 2003. In dealing with the COVID-19 pandemic, as a country with limited resources in the health system, it is very important to implement policies that are more preventive and anticipatory based on  past experience in dealing with pandemics.